Gevorg Tiratsyan - Tumanyan, Garegin (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Gevorg Tiratsyan was born on September 18, 1926, in the city of Chetatea-Alba, Romania. He was born to the family of the noteworthy pedagogue, Artashes Tiratsyan. In his school years, he was able to learn a number of European languages aside from the main subjects of history, Armenian, Russian, and Romanian. In 1945, he was admitted to the Department of History at Bucharest University. Shortly after, the Tiratsyans family repatriated to Armenia. In 1948, G. Tiratsyan was already a second-year student at Yerevan State University’s Department of History. After graduating, he was accepted into the PhD program in 1952, with Boris Piotrovski as his advisor. The internationally recognized scholar, Hovsep Orbeli, and the prominent representative of the orientalists of Leningrad, Camilla Trever, significantly influenced the wide-range of the future archaeologist’s scholarly interests.